2001
DOI: 10.1016/s0924-9338(01)00566-1
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic Study on schizophrenic patients living in the community. Subjective needs and perceived help

Abstract: In a community sample of 418 persons diagnosed with schizophrenia, subjective needs and perceived help was measured by the Camberwell Assessment of Need (CAN). The mean number of reported needs was 6.2 and the mean number of unmet needs 2.6. The prevalence of needs varied substantially between the need areas from 3.6% ('telephone') to 84.0% ('psychotic symptoms'). The rate of satisfaction estimated as the percentage of persons satisfied with the help provided within an area varied between 20.0% ('telephone') a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
62
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 13 publications
12
62
1
3
Order By: Relevance
“…Previous studies also found a low rate of adequacy in these particular domains (Hansson et al 1995;Middleboe et al 2001;Simons and Petch 2002). In our study, these needs are considered more unmet by consumers than by staff.…”
Section: Needs Assessmentsupporting
confidence: 62%
See 3 more Smart Citations
“…Previous studies also found a low rate of adequacy in these particular domains (Hansson et al 1995;Middleboe et al 2001;Simons and Petch 2002). In our study, these needs are considered more unmet by consumers than by staff.…”
Section: Needs Assessmentsupporting
confidence: 62%
“…In our study, accommodations ranked first and second in importance by consumers and staff, respectively. Generally, this domain is ranked between tenth and twelfth (Fleury et al 2008;Hansson et al 1995;Middleboe et al 2001;Ochoa et al 2003;Simons and Petch 2002). Food, money and looking after the home are also more highly rated by consumers and staff in our study.…”
Section: Needs Assessmentmentioning
confidence: 52%
See 2 more Smart Citations
“…This finding has been replicated in studies which had also reported a lack of social support, and unmet needs around social interaction and community belonging. 82,83 Studies which examined composition of social networks of individuals with psychosis had found them to contain fewer friends 46 and more service practitioners 84 than the general population, and the onset of psychosis can involve changes in social networks and the loss of friends. 85 It is the multifaceted and dynamic nature of social networks that this study explores, looking beneath a map of connections to understand the negotiated meaning, sets of choices, capacity for growth and qualities such as reciprocity.…”
Section: The Recovery Approachmentioning
confidence: 99%